Comparative evaluation of point-of-care blood gas analysis in rabbit disease models - Park, Soo Jeong; Cho, Seong Eun; Huy, Tran Xuan Ngoc; Kim, Suk; Kim, Sang Hun; Park, Beomjin (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aims to evaluate the blood gas results in various rabbit disease models and to establish the reference interval of venous and arterial blood gas parameters for clinically healthy and diseased rabbits. The primary purpose of this study is to evaluate various disease effects on acid-base and electrolyte disturbance and to examine the clinical value of blood gas analysis in rabbits.MethodsTwo hundred rabbits with various breeds were included in the study. Rabbits were divided into dental, gastrointestinal, musculoskeletal, and urologic disease model groups and one clinically healthy group. Venous and arterial blood gas analyses were performed with a point-of-care blood gas analyzer, i-Smart 300 VET Blood Gas Analyzer (i-SENSE, Korea). The reference intervals for the blood gas results were established. Reference intervals for each diseased group were compared with a clinically healthy control group to analyze the disease's effect on blood gas values.ResultsSeveral acid-base and electrolyte derangements were confirmed. The dental disease model had lower pH (power of hydrogen), PCO2 (partial pressure of carbon dioxide), and HCO3 (bicarbonate) than the control group (p-values < 0.001 by t-tests for both pH and HCO3, and p-value < 0.01 by a t-test for arterial PCO2). The gastrointestinal disease model demonstrated hyponatremia and hypocalcemia compared to the control group, with the p-values < 0.01 by t-tests for both sodium and calcium. The musculoskeletal disease model had lower Hct (hematocrit) and HGB (hemoglobin) than the control (p-values < 0.01 by t-tests for both Hct and HGB). The urologic disease group did not have a statistically significant difference in the reference interval of blood gas results.ConclusionsThe results indicated that various disease models in rabbits alter blood gas values. Diseases in body systems correlated with acid-base and electrolyte regulation are more likely to induce blood gas derangements. However, blood gas evaluation in various rabbit diseases is limited. Further studies with more cases in equivalent distribution and other disease models are needed.Clinical relevanceThis study is the first to present the reference interval for venous and arterial blood gas results in various disease models of rabbits. Also, this study presented the clinical value of point-of-care blood gas analysis in rabbit diseases. Blood gas analysis has potential diagnostic and prognostic value on various rabbit diseases.